Viscoelastic functional composite material, viscoelastic coating, viscoelastic diaphragm and preparation method thereof, and lithium ion battery
By applying viscoelastic functional composite materials on the lithium-ion battery separator, the problems of volume expansion and poor circulation performance of silicon-based materials in lithium-ion batteries are solved, and the cycle life and interface bonding effect of the battery are significantly improved.
Patent Information
- Application Number
- CN202411996965.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-18
AI Technical Summary
As the negative electrode material of lithium-ion batteries, silicon-based materials have problems such as large volume expansion and poor circulation performance, which leads to expansion and contraction and interface problems of the battery during operation, affecting electrical performance.
A viscoelastic functional composite material, including chemically modified coated viscoelastic materials and aqueous glue, is developed to coat the separator, impart viscoelasticity to the separator, improve the interface between the separator and the pole sheet and the shape and dimensional stability of the battery.
Through the use of viscoelastic separators, the electrical performance of silicon-based negative electrode lithium batteries is significantly improved, including cycle life, eases the expansion and contraction problem, improves the interface bonding effect, and maintains the stability of the battery shape and size.
Smart Images

Figure BDA0005225111820000131
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of viscoelastic coatings, and in particular relates to a viscoelastic functional composite material, a viscoelastic coating, a viscoelastic diaphragm and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries (LIBs) play a pivotal role in today's daily life due to their excellent energy density, cycle life, and rate performance. One of the key components that paved the way for the success of LIBs is the graphite anode material, which has become the main structure of the anode of lithium-ion batteries. However, the theoretical capacity of graphite is only 372mA / g, which can no longer meet the development needs of high-capacity and high-energy-density lithium-ion batteries. The theoretical capacity of silicon-based (e.g., silicon-carbon) anode materials (3572mA / g) is much higher than that of graphite. Silicon-based materials have become the most promising next-generation anode materials, but they have inherent defects such as large volume expansion and poor cycle performance. Summary of the invention
[0003] The purpose of the present invention is to provide a viscoelastic functional composite material, a viscoelastic coating, a viscoelastic diaphragm and a preparation method thereof, and a lithium ion battery. The viscoelastic functional composite material provided by the present invention can effectively improve the viscoelasticity of the diaphragm in the Z direction, endow the viscoelastic diaphragm with compressible and rebound properties, as well as bonding pole piece properties, effectively alleviate the expansion and contraction and interface problems existing in silicon-based negative electrode lithium batteries during operation, thereby significantly improving the electrical performance (including cycle life) of silicon-based negative electrode lithium batteries.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The present invention provides a viscoelastic functional composite material, comprising a chemically modified and coated viscoelastic material and a water-based glue; the shell layer of the chemically modified and coated viscoelastic material is a pressure-sensitive material with adhesive properties, and the core of the chemically modified and coated viscoelastic material is a polymer viscoelastic material; the mass percentage of the dry weight of the water-based glue to the dry weight of the chemically modified and coated viscoelastic material is 1 to 10%.
[0006] Preferably, the polymer viscoelastic material is composed of a soft segment and a hard segment; the glass transition temperature of the soft segment is less than -10°C, and the soft segment includes one or more of an ethyl acrylate segment, a n-butyl acrylate segment, an isobutyl acrylate segment, an isooctyl acrylate segment, a long-chain polyol segment, an isooctyl methacrylate segment, and a lauryl methacrylate segment;
[0007] The glass transition temperature of the hard segment is greater than 25° C., and the hard segment includes one or more of a vinyl acetate segment, a methyl acrylate segment, an acrylic acid segment, a methacrylic acid segment, a methyl methacrylate segment, a styrene segment, a hydroxyethyl methacrylate segment, an acrylamide segment, and an isocyanate segment;
[0008] The mass percentage of the hard segment in the macromolecular viscoelastic material is less than 20%.
[0009] Preferably, the pressure-sensitive material having adhesive properties comprises one or more of polyacrylate, polyurethane, polyvinyl chloride, polyvinyl ether, silicone resin, ethylene-vinyl acetate copolymer, polyvinyl alcohol and epoxy resin;
[0010] The mass percentage of the dry weight of the pressure-sensitive material with adhesive properties to the dry weight of the macromolecular viscoelastic material is 1-20%.
[0011] Preferably, the method for preparing the chemically modified coated viscoelastic material comprises the following steps:
[0012] Mixing a viscoelastic material, a first solvent, and a pressure-sensitive material having adhesive properties to obtain a mixed solution;
[0013] The mixed solution is spray-dried and airflow-pulverized in sequence to obtain the chemically modified and coated viscoelastic material;
[0014] The median particle size of the chemically modified and coated viscoelastic material is 0.2 to 10 μm.
[0015] Preferably, the aqueous adhesive comprises one or more of polyacrylic acid-butyl acetate copolymer emulsion, polyacrylic acid-methacrylate copolymer emulsion, polyacrylic acid-acrylonitrile copolymer solution and polyacrylonitrile-(2-ethylhexyl) copolymer emulsion.
[0016] Preferably, it also includes a second solvent and / or an auxiliary agent;
[0017] The second solvent includes one or more of water, ethanol and isopropanol, and the mass ratio of the chemically modified coated viscoelastic material to the second solvent is 1:3-50;
[0018] The auxiliary agent comprises one or more of a wetting agent, a leveling agent, a film-forming auxiliary agent, a defoaming agent and a foam suppressant. The mass percentage of the auxiliary agent in the viscoelastic functional composite material is 0.1-1%.
[0019] The present invention provides a viscoelastic coating, which is formed by the viscoelastic functional composite material described in the above technical solution.
[0020] The present invention provides a viscoelastic membrane, comprising a porous membrane substrate and a viscoelastic coating arranged on the surface of the porous membrane substrate, wherein the viscoelastic coating is formed by the viscoelastic functional composite material described in the above technical solution.
[0021] The present invention provides a method for preparing the viscoelastic diaphragm described in the above technical solution, comprising the following steps:
[0022] The viscoelastic functional composite material is coated on the surface of the porous diaphragm substrate to obtain the viscoelastic diaphragm.
[0023] The present invention provides a lithium ion battery, comprising the viscoelastic diaphragm described in the above technical solution or the viscoelastic diaphragm prepared by the preparation method described in the above technical solution.
[0024] Preferably, the negative electrode material is a silicon-based material.
[0025] The present invention provides a viscoelastic functional composite material, including a chemically modified and coated viscoelastic material and a water-based glue; the shell layer of the chemically modified and coated viscoelastic material is a pressure-sensitive material with adhesive properties, and the core of the chemically modified and coated viscoelastic material is a polymer viscoelastic material; the dry weight of the water-based glue accounts for 1-10% of the dry weight of the chemically modified and coated viscoelastic material. The present invention aims at the technical problems that silicon-based materials have large volume expansion and poor cycle performance as negative electrode materials for lithium-ion batteries. The present invention develops a viscoelastic functional composite material, which can be coated on a diaphragm to give the diaphragm viscoelasticity, so that the expansion and contraction problems of silicon-based negative electrode lithium batteries during operation can be improved or solved by the viscoelasticity of the diaphragm, thereby improving the interface between the diaphragm and the pole piece, improving the shape and size stability of the battery, releasing internal stress, and improving the battery cycle life.
[0026] Specifically: The present invention develops a viscoelastic functional composite material, forms a viscoelastic coating on the surface of a porous diaphragm substrate, thereby giving the diaphragm viscoelasticity, effectively solving the problem that the current diaphragm is incompressible in the Z direction and cannot alleviate the expansion and contraction and interface problems existing in the operation of silicon-based negative electrode lithium batteries. The viscoelastic functional composite material provided by the present invention is compounded by using a chemically modified and coated viscoelastic material and a water-based glue, and optimizing the mass ratio between the components. The obtained viscoelastic functional composite material can effectively improve the viscoelasticity of the diaphragm in the Z direction, improve the compression resilience and bonding properties of the diaphragm as a whole, so that the obtained viscoelastic diaphragm can be compressed and thinned to the limit under pressure conditions, and can rebound after the pressure is removed. At the same time, the viscoelastic coating bonds the diaphragm and the pole piece together to form a whole, thereby improving or solving the expansion and contraction problems existing in the operation of silicon-based negative electrode lithium batteries, maintaining the stability of the shape and size of the battery, improving the interface, and helping high-energy-density silicon-based negative electrodes to be widely used in power and energy storage batteries.
[0027] The present invention provides a viscoelastic membrane, comprising a porous membrane substrate and a viscoelastic coating disposed on the surface of the porous membrane substrate, wherein the viscoelastic coating is formed by the viscoelastic functional composite material described in the above technical solution. The present invention gives the viscoelastic membrane coating compressibility and resilience characteristics, as well as bonding pole piece characteristics, by superimposing the porous characteristics of the membrane on the viscoelastic coating, so that the expansion and contraction problems existing in silicon-based negative electrode lithium batteries during operation can be improved or solved by the viscoelasticity of the viscoelastic membrane, thereby improving the interface between the membrane and the pole piece, improving the shape and size stability of the battery, releasing internal stress, and improving the battery cycle life. DETAILED DESCRIPTION
[0028] The present invention provides a viscoelastic functional composite material, comprising a chemically modified and coated viscoelastic material and a water-based glue; the shell layer of the chemically modified and coated viscoelastic material is a pressure-sensitive material with adhesive properties, and the core of the chemically modified and coated viscoelastic material is a polymer viscoelastic material; the mass percentage of the dry weight of the water-based glue to the dry weight of the chemically modified and coated viscoelastic material is 1 to 10%.
[0029] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0030] The viscoelastic functional composite material provided by the present invention includes a chemically modified and coated viscoelastic material. In the present invention, the chemically modified and coated viscoelastic material has a core-shell structure, consisting of a core and a shell layer coated on the surface of the core. The shell layer of the chemically modified and coated viscoelastic material is a pressure-sensitive material with adhesive properties, and the core of the chemically modified and coated viscoelastic material is a polymer viscoelastic material.
[0031] In the present invention, the median particle size of the chemically modified coated viscoelastic material is preferably 0.2 to 10 μm. The median particle size of the chemically modified coated viscoelastic material is the median particle size of the secondary particles (soft agglomerates) of the chemically modified coated viscoelastic material agglomerates. In the present invention, the shape of the chemically modified coated viscoelastic material preferably includes one or more of a spherical shape, an ellipsoidal shape, and a rod shape.
[0032] In the present invention, the core of the chemically modified and coated viscoelastic material is a polymer viscoelastic material. The appearance of the polymer viscoelastic material preferably includes solid powder or emulsion. The solid content of the polymer viscoelastic material formed by the emulsion is preferably 1 to 100%, and not 100%. The glass transition temperature (Tg) of the polymer viscoelastic material is preferably lower than room temperature (25°C), so the polymer viscoelastic material is in a highly elastic state above room temperature. The Tg of the polymer viscoelastic material is more preferably <0°C, so that the polymer viscoelastic material can adapt to lower application temperatures. The polymer viscoelastic material is composed of a soft segment (rubber segment) and a hard segment (plastic segment); the soft segment has a large self-rotation ability, exhibits flexibility and toughness, and gives the polymer viscoelastic material high elasticity; the hard segment forms a crystalline micro-region, becomes a physical "cross-linking" point between molecules, and gives the polymer viscoelastic material hardness and rigidity. The soft segment can rebound and restore its shape after compression, and the hard segment is difficult to restore to its original shape after compression. The combination of the soft segment and the hard segment gives the polymer viscoelastic material viscoelasticity. The glass transition temperature of the soft segment is preferably less than -10°C, and the soft segment preferably includes one or more of ethyl acrylate segment, n-butyl acrylate segment, isobutyl acrylate segment, isooctyl acrylate segment, long-chain polyol segment, isooctyl methacrylate segment and lauryl methacrylate segment. The glass transition temperature of the hard segment is preferably greater than 25°C, and the hard segment preferably includes one or more of vinyl acetate segment, methyl acrylate segment, acrylic acid segment, methacrylic acid segment, methyl methacrylate segment, styrene segment, hydroxyethyl methacrylate segment, acrylamide segment and isocyanate segment. In the present invention, the mass percentage of the hard segment in the polymer viscoelastic material is preferably less than 20%, more preferably 1 to 15%, and can be 10%, 8% or 2% in the embodiment. The present invention can ensure that the polymer viscoelastic material has high elasticity by controlling the mass percentage of the hard segment in the polymer viscoelastic material.
[0033] In a specific embodiment of the present invention, the polymer viscoelastic material can be one or more of polyethyl acrylate-vinyl acetate, polyurethane and polyisooctyl acrylate-acrylamide. The solid content of the polyethyl acrylate-vinyl acetate is preferably 40%, and the mass proportion of the vinyl acetate segment (hard segment) in the polyethyl acrylate-vinyl acetate is preferably 10%. The solid content of the polyurethane is preferably 100%, and the mass proportion of the isocyanate segment (hard segment) in the polyurethane is preferably 8%. The solid content of the polyisooctyl acrylate-acrylamide is preferably 50%, and the mass proportion of the acrylamide (hard segment) in the polyisooctyl acrylate-acrylamide is preferably 2%.
[0034] In the present invention, the shell layer of the chemically modified coated viscoelastic material is a pressure-sensitive material with adhesive properties. In the present invention, the pressure-sensitive material with adhesive properties includes soft monomers and hard monomers, and the pressure-sensitive material preferably also includes functional monomers. The soft monomers in the pressure-sensitive material play a role in adhesion, the hard monomers play a role in enhancing cohesion, and the functional monomers (also known as functional group monomers) give the pressure-sensitive material cross-linking properties, which can further enhance the adhesive force, cohesion and tolerance of the pressure-sensitive material. In the present invention, the pressure-sensitive material preferably includes one or more of polyacrylate, polyurethane, polyvinyl chloride, polyvinyl ether, silicone resin, ethylene-vinyl acetate copolymer, polyvinyl alcohol and epoxy resin; in the embodiment, it can be one or more of polyurethane pressure-sensitive material, ethylene-vinyl acetate copolymer pressure-sensitive material and silicone resin pressure-sensitive adhesive. The polyurethane pressure-sensitive material is specifically a polyurethane emulsion, and the solid content is preferably 40%. The ethylene-vinyl acetate copolymer pressure-sensitive material is specifically an ethylene-vinyl acetate copolymer emulsion, and the solid content is preferably 20%. The organic silicone resin pressure-sensitive adhesive is specifically an organic silicone resin emulsion, and the solid content is preferably 20%.
[0035] In the present invention, the mass percentage of the dry weight of the pressure-sensitive material to the dry weight of the polymer viscoelastic material is preferably 1-20%, and in the embodiment it can be 10%.
[0036] In the present invention, the method for preparing the chemically modified coated viscoelastic material preferably comprises the following steps:
[0037] mixing a viscoelastic material, a first solvent and a pressure-sensitive material to obtain a mixed solution;
[0038] The mixed solution is spray-dried and airflow-pulverized in sequence to obtain the chemically modified and coated viscoelastic material.
[0039] The present invention mixes a viscoelastic material, a first solvent and a pressure-sensitive material to obtain a mixed solution. In the present invention, the first solvent preferably includes one or more of water, methanol, ethanol, isopropanol, ethylene glycol, glycerol, butanone and ethyl acetate, preferably at least two of water, methanol, ethanol, isopropanol, ethylene glycol, glycerol, butanone and ethyl acetate; when the first solvent is preferably two of the above solvents, the mass ratio of the two solvents is preferably (5-50): (15-55), and in the embodiment, it is specifically 10:50, 50:55 or 5:15. In the embodiment, it can be ethanol-water, butanone-ethyl acetate or ethylene glycol-water; the ethanol-water is a mixed solvent of ethanol and water, wherein the mass ratio of ethanol to water is preferably 10:50. The butanone-ethyl acetate is a mixed solvent of butanone and ethyl acetate, wherein the mass ratio of butanone and ethyl acetate is preferably 50:55. The ethylene glycol-water is a mixed solvent of ethylene glycol and water, wherein the volume ratio of ethylene glycol to water is preferably 5:15. The mass percentage of the dry weight of the pressure-sensitive material to the dry weight of the polymer viscoelastic material is preferably 1-20%, and in the embodiment it can be 10%. The ratio of the dry weight of the polymer viscoelastic material to the total mass of the dry weight of the polymer viscoelastic material and the first solvent is preferably 1:1-19, and in the embodiment it can be 1:2.5, 3:10 or 5:7. The mixing preferably includes: premixing the polymer viscoelastic material and the first solvent to obtain a premix; and finally mixing the premix and the pressure-sensitive material. The premixing is preferably carried out under stirring, and the rotation speed of the premixing stirring is preferably 100-500rpm, and in the embodiment it can be 500rpm, 400rpm or 200rpm, and the stirring time is preferably 0.1-0.5h, and in the embodiment it can be 0.2h, 0.5h or 0.1h. The final mixing is preferably carried out under stirring conditions, the speed of the final mixing stirring is preferably 800-1500 rpm, and in the embodiment it can be 1000 rpm, 800 rpm or 1200 rpm, and the stirring time is preferably 0.1-1 h, and in the embodiment it can be 0.5 h, 0.2 h or 1 h.
[0040] A mixed solution is obtained; the mixed solution is spray-dried and airflow-pulverized in sequence to obtain the chemically modified coated viscoelastic material. In the present invention, the spray drying temperature is preferably 50 to 120°C, and the time is preferably 3 to 30 minutes. The pressure of the airflow pulverization is preferably 0.7 to 0.85 MPa, and the gas used in the airflow pulverization preferably includes one or more of air, nitrogen and carbon dioxide, and the gas flow rate of the airflow pulverization is preferably 300 to 500 m / s.
[0041] The viscoelastic functional composite material provided by the present invention includes an aqueous glue. In the present invention, the aqueous glue can be an aqueous polymer emulsion or an aqueous polymer solution. The aqueous glue has amphiphilic properties, including a lipophilic segment and a hydrophilic segment, the lipophilic segment can have a good affinity with the diaphragm substrate, and the hydrophilic segment can be combined with the chemically modified and coated viscoelastic material, thereby acting as a bridge to firmly attach the chemically modified and coated viscoelastic material to the surface of the diaphragm substrate. The aqueous glue preferably includes one or more of polyacrylic acid-butyl acetate copolymer emulsion, polyacrylic acid-methacrylate copolymer emulsion, polyacrylic acid-acrylonitrile copolymer solution, and polyacrylonitrile-(2-ethylhexyl) copolymer emulsion. In the embodiment, it can be polyacrylic acid-acrylonitrile copolymer solution aqueous glue, polyacrylonitrile-(2-ethylhexyl) copolymer emulsion aqueous glue or polyacrylic acid-butyl acetate copolymer emulsion aqueous glue. The solid content of the polyacrylic acid-acrylonitrile copolymer solution aqueous glue is preferably 25%. The solid content of the polyacrylonitrile-(2-ethylhexyl) copolymer emulsion aqueous glue is preferably 40%. The solid content of the polyacrylic acid-butyl acetate copolymer emulsion water-based glue is preferably 25%.
[0042] In the present invention, the mass percentage of the dry weight of the water-based glue to the dry weight of the chemically modified and coated viscoelastic material is preferably 1-10%, and in the embodiments it can be 10%, 8% or 1.25%.
[0043] The viscoelastic functional composite material provided by the present invention preferably also includes a second solvent and / or an auxiliary agent. In the present invention, the second solvent preferably includes one or more of water, ethanol and isopropanol, more preferably at least two of water, ethanol and isopropanol, and the water is preferably deionized water. The mass ratio of the chemically modified coated viscoelastic material and the second solvent is preferably 1:3 to 50, and specifically 1:3, 1:9 or 1:49.3 in the embodiment. The auxiliary agent preferably includes one or more of a wetting agent, a leveling agent, a film-forming aid, a defoamer and an antifoaming agent, preferably at least two of a wetting agent, a leveling agent, a film-forming aid, a defoamer and an antifoaming agent. The wetting agent preferably includes a non-ionic polyether wetting agent, and the solid content of the non-ionic polyether wetting agent is preferably 100%, which can be AEO-7 in the embodiment. The leveling agent preferably includes a polyether-modified siloxane leveling agent and / or an alcohol ester twelve leveling agent, and the solid content of the polyether-modified siloxane leveling agent is preferably 100%. The film-forming aid preferably includes an alcohol ester film-forming aid. The defoamer preferably includes a modified silicone defoamer, and the solid content of the modified silicone defoamer is preferably 100%. In the embodiment, the defoamer is a polyether-modified silicone defoamer (8518). The antifoamer preferably includes a modified silicone antifoamer, and the solid content of the modified silicone antifoamer is preferably 100%. In the embodiment, the antifoamer is a fluorine-modified silicone antifoamer (AO-106). The mass percentage of the auxiliary agent in the viscoelastic functional composite material is preferably 0.1-1%, and in the embodiment it can be 0.2%, 0.5% or 0.1%.
[0044] The viscoelastic functional composite material provided by the present invention preferably includes a chemically modified and coated viscoelastic material, an aqueous glue and a second solvent; or the viscoelastic functional composite material preferably includes a chemically modified and coated viscoelastic material, an aqueous glue, a second solvent and an auxiliary agent. The solid content of the viscoelastic functional composite material is preferably 2 to 50%. When the viscoelastic functional composite material preferably also includes a second solvent or preferably also includes a second solvent and an auxiliary agent, the quality method of the viscoelastic functional composite material preferably includes: dispersing the chemically modified and coated viscoelastic material in the second solvent to obtain a chemically modified and coated viscoelastic material dispersion; stirring and mixing the chemically modified and coated viscoelastic material dispersion and the aqueous glue, when the viscoelastic functional composite material preferably includes an auxiliary agent, the stirred and mixed raw materials also include an auxiliary agent.
[0045] The present invention provides a viscoelastic coating, which is formed by the viscoelastic functional composite material described in the above technical solution. The viscoelastic coating provided by the present invention can be compressed and thinned to the limit under pressure conditions, and can rebound after the pressure is removed. The thickness of the viscoelastic coating is preferably 0.5 to 5 μm.
[0046] The preparation method of the viscoelastic coating provided by the present invention preferably comprises: coating the viscoelastic functional composite material on the surface of the substrate to obtain the viscoelastic coating on the surface of the substrate. In the present invention, the coating method preferably includes one or more of brush coating, roller coating and dip coating. In a specific embodiment of the present invention, the specific implementation method of the coating preferably includes one or more of a micro-gravure roller method, a wire rod method and a transfer coating method, and in the embodiment, it is specifically a micro-gravure roller method, a wire rod method, or a combination of a micro-gravure roller and a transfer coating method. The coating speed of the micro-gravure roller method is preferably 100 to 150 m / min. The coating speed of the wire rod method is preferably 100 to 120 m / min. The coating speed of the micro-gravure roller and the transfer coating method is preferably 100 to 120 m / min. After the coating is completed, a wet film is directly obtained, and the present invention preferably also includes: drying the wet film to obtain the viscoelastic coating. The drying temperature is preferably 70-85° C., preferably 70-75° C. or 75-85° C., and the drying time is preferably 15-18 s. The drying is preferably performed by hot air in an oven.
[0047] The viscoelastic functional composite material provided by the present invention is coated on a porous diaphragm to impart viscoelasticity to the diaphragm, in order to solve the current application pain points of the dry-process PP diaphragm and the wet-process PE diaphragm being incompressible in the Z direction and taking into account the bonding properties, but being unable to alleviate the expansion, contraction and interface problems existing in silicon-based negative electrode lithium batteries during operation.
[0048] The present invention provides a viscoelastic membrane, comprising a porous membrane substrate and a viscoelastic coating arranged on the surface of the porous membrane substrate, wherein the viscoelastic coating is formed by the viscoelastic functional composite material described in the above technical solution.
[0049] The viscoelastic membrane provided by the present invention includes a porous membrane substrate. In the present invention, the porous membrane substrate preferably includes a dry PP membrane or a wet PE membrane. The thickness of the porous membrane substrate is preferably 5 to 25 μm, and in the embodiment, it can be 12 μm or 9 μm; the porosity is preferably 35 to 55%, and in the embodiment, it can be 50% or 42%.
[0050] The viscoelastic membrane provided by the present invention comprises a viscoelastic coating disposed on the surface of the porous membrane substrate, wherein the viscoelastic coating is formed by the viscoelastic functional composite material described in the above technical solution. In the present invention, the viscoelastic coating is disposed on the surface of the porous structure membrane, and the formed viscoelastic coating has a porous structure.
[0051] In the present invention, the viscoelastic coating is preferably disposed on one or both surfaces of the floating diaphragm. The single-layer thickness of the viscoelastic coating (any surface of the porous diaphragm) is preferably 0.5 to 5 μm, preferably 5 μm or 3 μm. The double-sided thickness of the viscoelastic coating (the sum of the thickness of the two surfaces of the porous diaphragm) is preferably 1 to 10 μm.
[0052] In the present invention, the viscoelastic coating imparts compressive resilience and viscosity to the porous diaphragm substrate in the Z direction. The viscoelastic coating formed on the surface of the porous diaphragm by the viscoelastic functional composite material significantly improves the diaphragm 0.5-1.0MPa compression deformation, the viscoelastic coating rebound rate and the adhesion between the diaphragm and the pole piece, and is applied to silicon-carbon negative electrode batteries: the battery internal resistance is small, the battery shape and dimensional stability is improved, the interface bonding effect is good, and the interface between the diaphragm and the pole piece is improved. The viscoelastic coating can be compressed and rebounded, thereby releasing the internal stress caused by the charging and discharging of the battery cell, thereby improving the battery cycle life. Among them, the resilience of the viscoelastic coating satisfies: under the conditions of 20-40°C, the deformation can be compressed by more than 50% under a pressure of 0.5MPa, and the deformation can be compressed by more than 70% under a pressure of 1MPa. When the pressure is removed, it can rebound to more than 80% of the original thickness. The adhesion of the viscoelastic coating meets the following requirements: under the conditions of 20-40°C, pressure of 5MPa, pressurization time of 40-60s, the adhesion between the coating and the cathode electrode of the ternary material is ≥3N / m.
[0053] The present invention provides a method for preparing the viscoelastic diaphragm described in the above technical solution, comprising the following steps:
[0054] The viscoelastic functional composite material is coated on the surface of the porous diaphragm substrate to obtain the viscoelastic diaphragm.
[0055] In the present invention, the coating method preferably includes one or more of brush coating, roller coating and dip coating. In a specific embodiment of the present invention, the specific implementation of the coating preferably includes one or more of a micro-gravure roller method, a wire rod method and a transfer coating method, and in the embodiment, it is specifically a micro-gravure roller method, a wire rod method, or a combination of a micro-gravure roller and a transfer coating method. The coating speed of the micro-gravure roller method is preferably 100 to 150 m / min. The coating speed of the wire rod method is preferably 100 to 120 m / min. The coating speed of the micro-gravure roller and transfer coating method is preferably 100 to 120 m / min.
[0056] After the coating is completed, a wet film is directly obtained. The present invention preferably further comprises: drying the wet film to obtain the viscoelastic membrane. The drying temperature is preferably 70 to 85°C, preferably 70 to 75°C or 75 to 85°C, the time is preferably 15 to 18 seconds, and the drying is preferably carried out in an oven by hot air drying.
[0057] The present invention provides a lithium ion battery, comprising the viscoelastic diaphragm described in the above technical solution or the viscoelastic diaphragm prepared by the preparation method described in the above technical solution.
[0058] In the present invention, the lithium ion battery is preferably a lithium ion battery, and the negative electrode material of the lithium ion battery is a silicon-based material. The silicon-based material preferably includes a silicon-carbon material.
[0059] The present invention adopts a high-porosity PP or PE diaphragm substrate, and coats the viscoelastic functional composite material described in the above technical solution on the surface of the diaphragm to form a viscoelastic coating. The viscoelastic coating is composed of the viscoelastic functional composite material described in the above technical solution. At the same time, the diaphragm substrate has a porous property, and the viscoelastic coating also has a porous property. The viscoelastic material superimposes the porous property to give the viscoelastic coating compressible and rebound properties, as well as bonding pole piece properties. The viscoelastic functional composite material is coated with the substrate to form an integral structure, which can effectively improve the viscoelasticity of the diaphragm in the Z direction, and improve the overall compression resilience and bonding properties of the diaphragm. The obtained viscoelastic diaphragm can be compressed and thinned to the limit under a certain pressure, and can rebound at a certain proportion after the pressure is removed. At the same time, the viscoelastic coating bonds the diaphragm and the pole piece together to form a whole, thereby improving or solving the expansion and contraction problems of silicon-based negative electrode lithium batteries during operation, maintaining the stability of the shape and size of the battery, improving the interface, and facilitating the large-scale application of high-energy-density silicon-based negative electrodes in power and energy storage batteries.
[0060] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0061] All “parts” in the following examples are “parts by mass”.
[0062] Example 1
[0063] This embodiment provides a method for preparing a viscoelastic functional slurry, comprising the following steps:
[0064] S1. Modification of viscoelastic materials:
[0065] 100 parts of polyethyl acrylate-vinyl acetate (vinyl acetate (hard segment) accounts for 10% by mass) emulsion with a solid content of 40% are added to a mixed solvent composed of 10 parts of ethanol and 50 parts of water, and stirred evenly (stirring speed 500 rpm, stirring time 0.2 h), and then 10 parts of polyurethane pressure-sensitive material emulsion with a solid content of 40% are added; high-speed stirring is uniformly performed (stirring speed 1000 rpm, stirring time 0.5 h), and then continuously subjected to spray drying (drying temperature 95°C, time 10 min) and air flow crushing (air pressure 0.8 MPa, gas is dry air, air flow speed: 350 m / s) processes, cooled and allowed to stand, to obtain a spherical chemically modified coated viscoelastic material powder (material B) with a median particle size of 6.5 μm.
[0066] S2. Preparation of viscoelastic functional slurry:
[0067] The 40 parts of B material powder prepared above were added into a mixed solvent consisting of 10 parts of isopropanol and 110 parts of water, and 12.8 parts of a polyacrylic acid-acrylonitrile copolymer solution (aqueous glue) with a solid content of 25%, 0.2 parts of a wetting agent non-ionic polyether wetting agent (AEO-7) with a solid content of 100%, 0.1 parts of a modified silicone defoamer with a solid content of 100% (polyether modified silicone defoamer 8518) and 0.1 parts of a polyether modified siloxane leveling agent with a solid content of 100% were added, and stirred thoroughly to obtain a functional slurry (C slurry) with a solid content of about 25%.
[0068] S3. Preparation of viscoelastic membrane:
[0069] The above C slurry was coated on the surface of the dry PP diaphragm by a micro-gravure roller. The PP diaphragm had a thickness of 12 μm, a porosity of 50%, a single layer thickness of the viscoelastic coating of 5 μm, and a coating speed of 100 m / min. The diaphragm coating was hot-air dried in an oven at a drying temperature of 70 to 75°C and a drying time of 15 s.
[0070] Example 2
[0071] This embodiment provides a method for preparing a viscoelastic functional slurry, comprising the following steps:
[0072] S1. Modification of viscoelastic materials:
[0073] 45 parts of polyurethane solid with a solid content of 100% (isocyanate (hard segment) accounts for 8% by mass) are added to a mixed solvent consisting of 50 parts of butanone and 55 parts of ethyl acetate, and stirred evenly (stirring speed 400 rpm, stirring time 0.5 h), and then 22.5 parts of ethylene-vinyl acetate copolymer (pressure-sensitive adhesive) solution with a solid content of 20% are added; high-speed stirring is performed evenly (stirring speed 1200 rpm, stirring time 1.0 h), and then spray drying (drying temperature 80°C, time 20 min) and air flow crushing (air pressure 0.75 MPa, gas is nitrogen, air flow speed: 450 m / s) are continuously performed, and the mixture is cooled and allowed to stand to obtain a spherical chemically modified and coated viscoelastic material powder (material B) with a median particle size of 6.0 μm.
[0074] S2. Preparation of viscoelastic functional slurry:
[0075] The 20 parts of the B material powder prepared above are added to a mixed solvent consisting of 10 parts of ethanol and 170 parts of water, and 5 parts of polyacrylonitrile-(2-ethylhexyl ester) copolymer emulsion (aqueous glue) with a solid content of 40%, 0.6 parts of a wetting agent non-ionic polyether wetting agent (AEO-9) with a solid content of 100%, 0.2 parts of a modified organic silicone antifoam agent with a solid content of 100% (fluorine-modified organic silicone antifoam agent AO-106) and 0.2 parts of an alcohol ester twelve leveling agent with a solid content of 100% are added, and stirred thoroughly to obtain a functional slurry (C slurry) with a solid content of about 11%.
[0076] S3. Preparation of viscoelastic membrane:
[0077] The C slurry was coated on the surface of a wet PE diaphragm by a wire rod method. The PE diaphragm had a thickness of 9 μm, a porosity of 42%, a single layer thickness of the viscoelastic coating of 3 μm, and a coating speed of 120 m / min. The diaphragm coating was hot-air dried in an oven at a drying temperature of 75 to 85°C and a drying time of 18 s.
[0078] Example 3
[0079] This embodiment provides a method for preparing a viscoelastic functional slurry, comprising the following steps:
[0080] S1. Modification of viscoelastic materials:
[0081] 100 parts of poly(2-ethylhexyl)acrylate-acrylamide (acrylamide (hard segment) accounts for 2% by mass) solid with a solid content of 50% are added to a mixed solvent consisting of 5 parts of ethylene glycol and 15 parts of water, and stirred evenly (stirring speed 200 rpm, stirring time 0.1 h), and then 2.5 parts of silicone resin (pressure-sensitive adhesive) solution with a solid content of 20% are added; stirred evenly at high speed (stirring speed 800 rpm, stirring time 0.2 h), and then continuously subjected to spray drying (drying temperature 120°C, time 30 min) and air flow crushing (air pressure 0.85 MPa, gas is air, air flow speed: 400 m / s) processes, cooled and allowed to stand, to obtain a chemically modified and coated viscoelastic material powder (material B) with a median particle size of 10.0 μm and a core-shell spherical shape.
[0082] S2. Preparation of viscoelastic functional slurry:
[0083] The 80 parts of the B material powder prepared above were added into a mixed solvent consisting of 600 parts of ethanol, 850 parts of isopropanol and 2500 parts of water, and 4 parts of polyacrylic acid-butyl acetate copolymer emulsion (water-based glue) with a solid content of 25%, 0.05 parts of a polyether-modified siloxane leveling agent with a solid content of 100% and 0.05 parts of a modified silicone defoamer with a solid content of 100% (polyether-modified silicone defoamer 8518) were added, and stirred thoroughly to obtain a functional slurry (C slurry) with a solid content of about 2%.
[0084] S3. Preparation of viscoelastic membrane:
[0085] The above C slurry was coated on the surface of the wet PE diaphragm by micro-gravure roller + transfer coating. The PE diaphragm had a thickness of 9 μm, a porosity of 42%, a single layer thickness of the viscoelastic coating of 3 μm, and a coating speed of 120 m / min. The diaphragm coating was hot-air dried in an oven at a drying temperature of 75-85°C and a drying time of 18 s.
[0086] Comparative Example 1
[0087] The difference between Comparative Example 1 and Example 1 is that step S1 is omitted, that is, the viscoelastic material is not chemically modified, and material A is directly used to replace material B for slurry preparation. The remaining components and preparation method are the same as those in Example 1.
[0088] Comparative Example 2
[0089] The difference between Comparative Example 2 and Example 1 is that in step S1, the viscoelastic material (polyethyl acrylate-vinyl acetate) is replaced with a pure acrylic acid polymer (non-viscoelastic material), and the remaining components and preparation method are the same as those in Example 1.
[0090] Comparative Example 3
[0091] The difference between Comparative Example 3 and Example 1 is that the aqueous glue component is omitted in step S2, and the remaining components and preparation method are the same as those in Example 1.
[0092] Comparative Example 4
[0093] The difference between Comparative Example 4 and Example 1 is that step S3 adopts a spraying method with a spot coverage rate of 15%, and the remaining components and preparation methods are the same as those of Example 1.
[0094] Comparative Example 5
[0095] The dry-process PP separator of Example 1 was used without any coating process. The PP separator had a thickness of 12 μm and a porosity of 50%.
[0096] Comparative Example 6
[0097] The difference between Comparative Example 6 and Example 1 is that step S1 is omitted, that is, the viscoelastic material is not subjected to separate chemical modification and coating, but the materials of step S1 (including polymer viscoelastic material and pressure-sensitive adhesive material) are directly added to step S2 for blending and slurry preparation, and the remaining components and preparation method are the same as those of Example 1.
[0098] Specifically:
[0099] S1. Preparation of viscoelastic functional slurry:
[0100] 90 parts of polyethyl acrylate-vinyl acetate (vinyl acetate (hard segment) accounts for 10% by mass) with a solid content of 40%, 10 parts of polyurethane pressure-sensitive material emulsion with a solid content of 40%, are added to a mixed solvent consisting of 10 parts of isopropanol and 60 parts of water, and 12.8 parts of polyacrylic acid-acrylonitrile copolymer solution (water-based glue) with a solid content of 25%, 0.2 parts of a wetting agent non-ionic polyether wetting agent (AEO-7) with a solid content of 100%, 0.1 parts of a modified silicone defoamer with a solid content of 100% (polyether-modified silicone defoamer 8518) and 0.1 parts of a polyether-modified siloxane leveling agent with a solid content of 100% are added, and stirred thoroughly to obtain a functional slurry (C slurry) with a solid content of about 25%.
[0101] S2. Preparation of viscoelastic membrane:
[0102] The above C slurry was coated on the surface of the dry PP diaphragm by a micro-gravure roller. The PP diaphragm had a thickness of 12 μm, a porosity of 50%, a single layer thickness of the viscoelastic coating of 5 μm, and a coating speed of 100 m / min. The diaphragm coating was hot-air dried in an oven at a drying temperature of 70 to 75°C and a drying time of 15 s.
[0103] Thermal Pressure Test
[0104] The six groups of lithium battery separators and NCM911 pole pieces in the above three embodiments and six comparative examples were subjected to hot pressing test, and the hot pressing conditions were: room temperature, pressure 5 MPa, and pressing time 40 s.
[0105] Battery performance test
[0106] The nine groups of lithium battery separators in the above three embodiments and six comparative examples were made into square aluminum shell lithium ion batteries with a rated capacity of 314Ah, positive electrode NCM911, negative electrode: silicon carbon negative electrode; electrolyte: EC / EMC=3 / 7 (v / v), 1M LiPF 6 , VC2%.
[0107] The thickness, air permeability, compression deformation of the viscoelastic coating, rebound rate of the viscoelastic coating, and bonding strength of the pole piece of the lithium ion battery separators of Examples 1 to 3 and Comparative Examples 1 to 6 were measured; after the separators were made into batteries, the internal resistance, interface, and cycle life performance of the batteries were measured. The test results are shown in Table 1. Among them, the bonding strength of the pole piece was measured at 0 to 40°C, a pressure of 5 MPa, and a pressurization time of 40 to 60 seconds to measure the bonding strength between the coating and the pole piece.
[0108] Table 1 Performance test results of the diaphragm products obtained in Examples 1 to 3 and Comparative Examples 1 to 6
[0109]
[0110] As shown in Table 1, Example 1 prepares a functional slurry through a better formula combination and process. The viscoelastic functional coating diaphragm manufactured by coating it on the diaphragm has the best comprehensive physical and chemical properties: moderate thickness, good air permeability, large compression deformation of the viscoelastic coating, high rebound rate of the viscoelastic coating, and good electrode adhesion. The viscoelastic functional coating diaphragm manufactured from the slurry of Example 1 is used in batteries and has the best comprehensive battery performance: small internal resistance of the battery, good interface bonding effect, and high conventional 1000 cycle capacity retention rate.
[0111] In Example 2, with the change of slurry formula and the thinning of coating thickness to 3.0μm, the 0.5-1.0MPa compression deformation of the manufactured viscoelastic functional coating diaphragm and the rebound rate of the viscoelastic coating both decreased to varying degrees, and the electrode bonding force decreased; the internal resistance of the battery manufactured by the diaphragm of Example 2 became larger, the interface bonding effect became worse, and the conventional 1000 cycle capacity retention rate decreased, which is not preferred.
[0112] In Example 3, with the combination changes in the slurry formula, the 0.5-1.0 MPa compression deformation of the manufactured viscoelastic functional coating diaphragm and the rebound rate of the viscoelastic coating also decreased to varying degrees, and the electrode bonding force was further reduced; the internal resistance of the battery manufactured with the diaphragm of Example 3 became larger, the interface bonding effect was average, and the conventional 1000 cycle capacity retention rate decreased, which was close to the performance and application effect of Example 2, and was not preferred.
[0113] Compared with Example 1, due to the lack of chemical modification of the viscoelastic material, the adhesion between the viscoelastic functional coating diaphragm manufactured from the slurry of Comparative Example 1 and the electrode is significantly reduced. The battery interface bonding effect manufactured from the diaphragm of Comparative Example 1 is poor, and the conventional 1000 cycle capacity retention rate is reduced.
[0114] Compared with Example 1, in Comparative Example 2, the viscoelastic material is replaced with a pure acrylic polymer (non-viscoelastic material). The viscoelastic functional coating manufactured from the slurry of Comparative Example 2 has almost lost the 0.5-1.0 MPa compression deformation and the rebound rate of the viscoelastic coating, which leads to an increase in the internal resistance of the battery, poor interface bonding effect, and a significant decrease in the conventional 1000 cycle capacity retention rate.
[0115] Compared with Example 1, in Comparative Example 3, the aqueous glue component is omitted in step S2, that is, no glue is added to the functional slurry, because the role of the glue is to firmly attach the coating to the diaphragm. The absence of glue leads to a significant decrease in the adhesion between the viscoelastic functional coating diaphragm manufactured by the slurry of Comparative Example 3 and the electrode, an increase in the internal resistance of the battery, a poor interface bonding effect, and a significant decrease in the conventional 1000 cycle capacity retention rate.
[0116] Compared with Example 1, in Comparative Example 4, step S3 adopts spraying method, and the spot coverage rate is 15%; spraying can reduce the problem of coating pore blocking, but due to the lower coverage rate, the adhesion between the viscoelastic functional coating diaphragm manufactured by the slurry of Comparative Example 4 and the electrode is significantly reduced, and the other properties are less affected.
[0117] Comparative Example 5 directly uses a dry-process PP diaphragm with a thickness of 12μ without any processing. The 0.5-1.0MPa compression deformation of the diaphragm, the rebound rate of the viscoelastic coating, and the adhesion between the diaphragm and the electrode are all 0, so there is no interface bonding effect. The conventional 1000 cycle capacity retention rate is average and is not preferred.
[0118] Compared with Example 1, in Comparative Example 6, step S1 is omitted, that is, the viscoelastic material is not subjected to separate chemical modification and coating, and a core-shell structure cannot be formed; in step S2, the materials of step S1 (including polymer viscoelastic material and pressure-sensitive adhesive material) are directly added to be blended and prepared, and the pressure-sensitive adhesive fails to completely wrap the surface of the polymer viscoelastic material, resulting in a decrease in the electrode adhesion of the material, and a decrease in the adhesion between the viscoelastic functional coating diaphragm manufactured by the slurry of Comparative Example 6 and the electrode, resulting in an increase in the internal resistance of the battery, a poor interface bonding effect, and a decrease in the conventional 1000 cycle capacity retention rate.
[0119] From the test results of the diaphragms prepared in the above embodiments and comparative examples, it can be seen that the functional slurry provided by the present invention and the viscoelastic functional coating manufactured by coating the functional slurry on the diaphragm have a great influence on the performance of the diaphragm. The functional slurry is chemically modified by the viscoelastic material, and the slurry is prepared and coated to produce a viscoelastic functional coating diaphragm. The formula and process combination of the functional slurry provided by the present invention have unique technology, and the components or processes therein cannot be replaced or reduced at will.
[0120] In summary, the present invention provides a viscoelastic functional composite material, and carries out the preparation of viscoelastic diaphragms and the testing of the performance of applied battery cells. The results show that the viscoelastic coating formed by the viscoelastic functional composite material on the surface of the porous diaphragm significantly improves the 0.5-1.0 MPa compression deformation of the diaphragm, the rebound rate of the viscoelastic coating and the adhesion between the diaphragm and the pole piece. It is applied to silicon-carbon negative electrode batteries: the battery has low internal resistance, improves the shape and dimensional stability of the battery, has good interface bonding effect, improves the interface between the diaphragm and the pole piece, and the viscoelastic coating can be compressed and rebounded, thereby releasing the internal stress caused by the charging and discharging of the battery cell, thereby improving the battery cycle life.
[0121] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A viscoelastic functional composite material, characterized in that: It comprises a chemically modified coated viscoelastic material and a water-based glue; the shell layer of the chemically modified coated viscoelastic material is a pressure-sensitive material with adhesive properties, and the core of the chemically modified coated viscoelastic material is a polymer viscoelastic material; The mass percentage of the dry weight of the water-based glue to the dry weight of the chemically modified and coated viscoelastic material is 1-10%.
2. The viscoelastic functional composite material according to claim 1, characterized in that: The polymer viscoelastic material is composed of a soft segment and a hard segment; the glass transition temperature of the soft segment is less than -10°C, and the soft segment includes one or more of an ethyl acrylate segment, a n-butyl acrylate segment, an isobutyl acrylate segment, an isooctyl acrylate segment, a long-chain polyol segment, an isooctyl methacrylate segment, and a lauryl methacrylate segment; The glass transition temperature of the hard segment is greater than 25° C., and the hard segment includes one or more of a vinyl acetate segment, a methyl acrylate segment, an acrylic acid segment, a methacrylic acid segment, a methyl methacrylate segment, a styrene segment, a hydroxyethyl methacrylate segment, an acrylamide segment, and an isocyanate segment; The mass percentage of the hard segment in the macromolecular viscoelastic material is less than 20%.
3. The viscoelastic functional composite material according to claim 1, characterized in that: The pressure-sensitive material with adhesive properties includes one or more of polyacrylate, polyurethane, polyvinyl chloride, polyvinyl ether, silicone resin, ethylene-vinyl acetate copolymer, polyvinyl alcohol and epoxy resin; The mass percentage of the dry weight of the pressure-sensitive material with adhesive properties to the dry weight of the macromolecular viscoelastic material is 1-20%.
4. The viscoelastic functional composite material according to any one of claims 1 to 3, characterized in that: The preparation method of the chemically modified coated viscoelastic material comprises the following steps: Mixing a viscoelastic material, a first solvent, and a pressure-sensitive material having adhesive properties to obtain a mixed solution; The mixed solution is spray-dried and airflow-pulverized in sequence to obtain the chemically modified and coated viscoelastic material; The median particle size of the chemically modified and coated viscoelastic material is 0.2 to 10 μm.
5. The viscoelastic functional composite material according to claim 1, characterized in that: The water-based adhesive includes one or more of polyacrylic acid-butyl acetate copolymer emulsion, polyacrylic acid-methacrylate copolymer emulsion, polyacrylic acid-acrylonitrile copolymer solution and polyacrylonitrile-(2-ethylhexyl) copolymer emulsion.
6. The viscoelastic functional composite material according to claim 1, characterized in that: Also includes a second solvent and / or an auxiliary agent; The second solvent includes one or more of water, ethanol and isopropanol, and the mass ratio of the chemically modified coated viscoelastic material to the second solvent is 1:3-50; The auxiliary agent comprises one or more of a wetting agent, a leveling agent, a film-forming auxiliary agent, a defoaming agent and a foam suppressant. The mass percentage of the auxiliary agent in the viscoelastic functional composite material is 0.1-1%.
7. A viscoelastic coating, characterized in that: The viscoelastic functional composite material is formed from the viscoelastic functional composite material according to any one of claims 1 to 6.
8. A viscoelastic membrane, characterized in that: The invention comprises a porous membrane substrate and a viscoelastic coating arranged on the surface of the porous membrane substrate, wherein the viscoelastic coating is formed by the viscoelastic functional composite material according to any one of claims 1 to 6.
9. The method for preparing the viscoelastic membrane according to claim 8, characterized in that: The following steps are involved: The viscoelastic functional composite material is coated on the surface of the porous diaphragm substrate to obtain the viscoelastic diaphragm.
10. A lithium ion battery, characterized in that: The invention comprises the viscoelastic membrane according to claim 8 or the viscoelastic membrane prepared by the preparation method according to claim 9.
Citation Information
Cited By
Low-expansion and high-compaction graphite-based composite secondary particle as well as preparation method and application thereof
CN121054673A